Inventory of plants by the community of Waur Village, Kei Besar District, Maluku Province - Hastuti Hastuti; Hasria Alang; Ahmad Hasyim (Program Studi Pendidikan Biologi, Pascasarjana, Universitas Pattimura, 2022)
Indonesia is one of the countries with very diverse natural resources, including the richness of plant species. The ancestors of the Indonesian people have used these natural resources very wisely, such as knowledge about traditional medicine. Indonesia is also inhabited by around 300-700 ethnic groups, each ethnic group has a different culture, tradition and local wisdom. This study aims to determine the types of medicinal plants, the organs used and how to process medicinal herbs by the people of Waur Village, District. Kei Besar, Southeast Maluku Regency, Maluku Province. This research is a qualitative descriptive study with data collection techniques through observation, interviews and documentation. The research data were then analyzed descriptively and presented in the form of descriptions and tables. The results of the study show that there are 20 species of plants that are used by the people of Waur Village, Maluku Province. The most widely used organs are leaves and the most widely used method of processing ingredients is boiling.